A clinical study on the effectiveness of lignocaine preconditioning to treat protamine-induced catastrophic pulmonary vasoconstriction in paediatric cardiac surgery : Effectiveness of lignocaine to treat protamine-induced catastrophic pulmonary vasoconstriction - Singh, Sanjeev; Deigheidy Ehab Mahrous; Mustafa Mohammad Ateequr Rahman; Singh, Arti (Journal of the Portuguese Society of Anesthesiology, 2025)
Background: Protamine is a peptide rich in arginine and highly alkaline. When intravenously injected, protamine interacts with the polyanionic heparin to form a neutral charge, which isolates heparin from antithrombin III and leads to the loss of its anticoagulating properties. Therefore, protamine has been often used in cardiac surgeries to counteract anticoagulating unfractionated heparin. Methods: This was a single-centre, prospective, double-blind, and randomised study conducted among eight-eight paediatric patients with acyanotic congenital cardiac disease, scheduled for elective on-pump cardiac surgery under general anaesthesia. In this study, the participants were divided into four groups: group I- non-pulmonary hypertension with lignocaine preconditioning; group II – non-pulmonary hypertension with normal saline (as a placebo); group III- pulmonary hypertension with lignocaine preconditioning; and group IV- pulmonary hypertension with normal saline (as a placebo). Results: Pulmonary vasoconstriction occurred in 9.09% of cases after protamine administration. Both the II and IV groups exhibited an increase in mean airway pressure (Paw), respiratory index (RI), alveolar-arterial oxygen difference (A-aDO2), pulmonary artery pressure (PAP), and decreased dynamic pulmonary compliance (Cydn) and oxygen index (OI) after protamine administration. However, these changes were not observed in the I and III groups with lignocaine preconditioning. Plasma levels of TXB2 in the II and IV groups were higher than in the I and III groups, but 6-keto-PGF1 alpha levels were lower in the II and IV groups than in the I and III groups. Conclusion: Most congenital corrective cardiac surgeries are not possible without cardiopulmonary bypass and heparin. Lignocaine preconditioning reverses protamine-induced pulmonary vasoconstriction and improves pulmonary function before reversing unfractionated heparin with protamine.